ANALISIS PENERAPAN DAN PEMAHAMAN PRINSIP BISNIS SYARIAH BAGI UMKM DI KOTA BAUBAU - Tri Ulfyana (JISEF : Journal Of International Sharia Economics And Financial, 2022)
This study aims to determine the level of understanding and application of sharia business principles. The data used are primary and secondary data obtained by observation, interview, and documentation. The analysis tool used is descriptive. Based on the results of the study it was found that the level of understanding of sharia business principles classified as understanding was 82.66 percent. While those who do not understand are 17.33 percent. Aspects that are understood by the understanding of the need for mutual consent and the belief that business is part of worship to Allah Subhanahu Wata'ala. While the level of application of sharia business principles, that those who apply are 81.2 percent while those who do not apply are 18.8 percent. The most applied principles are shiddiq and tabligh. Grocery traders who have understood sharia principles better have also applied sharia business principles, especially in the buying and selling process, but not all have applied sharia business principles properly in accordance with the business principles of Rasulullah Shallahu'alaihi Wassalam.